(untitled) (Philological Studies, 2019)
The work is dedicated to the analysis of the spy novels written during the period of the “cold” war, which contributed much to the forming of the spy novel genre. In the investigation presented the attempt to analyze the development of the spy novel genre, its ideological background during the war time made in the context of the historical events, taking into account the fact of belonging the author to the Great Britain State Intelligence service. The focus of the analysis is concentrated on the new forms of realization of the plot vector and the modification of the protagonist.